Efektifitas Blog Guru Memandu Pengamatan Indera secara langsung melalui Model Pembelajaran Jig Saw di SMP Xaverius I jambi - Hastuti Wibowo (Universitas Jambi, 2012)
Internet blog can be utilized to assist learning in the classroom. The effectiveness of blog in learning was studied through a class room action research by using Jig Saw learning model. The results show that teachers' use of blogs in guiding the work of students in observing human sense through a model of Jig Saw can raise the average value of the working group from 68 to 83 (21% increase). Blog also helps the group work of below average students, indicated by the value of Q1 which is increased from 61 to 80 (31%). Individual use of sense learning material in blog also helps students understand the learning concepts, process skills, and apply them in everyday life, especially in keeping the senses healthy. The results of individual evaluation showed an increase from 68 to 81.